Malaria in Sudan: past, present and the future - Malik, Elfatih Mohamed; Khalafalla, Osman (Gezira Journal of Health Sciences, 2004)
Summary. Malaria is a major public health problem in Sudan and this is the leading cause of death. A lot of efforts are done recently to decrease the prevalence adopting the RBM initiative with its well known six elements. There is a new protocol for treatment which would be launched in June 2004. Malaria Burden. Malaria in Sudan is a major public Health Problem. It leads to an estimated 7.5- 10 million cases and 35000 deaths every year. The burden of the disease on the health system is a reality. Out of the total outpatients’ attendance, admissions and deaths malaria represents 20- 40% , 30-50% and 15-20% respectively. These figures bring Sudan on the top of WHO / EMRO countries, as Sudan shouldered 50% of cases and 70% of deaths in the region (WHO/EMRO). Malaria is endemic throughout the Sudan. The endemicity level varies from hypo-endemic in the north - mesoendemic in the central part and hyper-and holo-endemic in the south. (Map 1). Considering other factors which serve as a background for malaria in Sudan; metriological, human behavior and activities, status of the control programme, country economic and social conditions, Sudan has been stratified to 5 strata (Map2). It is worth to mention here that 80% of the populations are living in epidemic-prone area-unstable malaria transmission.